Розвиток ринку органічної продукції в Україні: проблеми, перспективи та шляхи їх вирішення - Багорка, Марія Олександрівна; Bagorka, Mariya; Якубенко, Юлія Леонідівна; Yakubenko, Yuliia (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2025)
У статті досліджено значення органічної продукції для сталого розвитку сільського господарства. Розкрито основні переваги органічних продуктів, які зумовлюють зростання попиту на внутрішньому та зовнішньому ринках, зокрема екологічна чистота, натуральність і позитивний вплив на здоров'я. Проаналізовано ключові проблеми розвитку ринку органічної продукції в Україні, серед яких висока вартість сертифікації, недостатня обізнаність споживачів, логістичні труднощі та складність відповідності міжнародним стандартам. Обґрунтовано необхідність впровадження державної підтримки, зокрема субсидій, пільгового кредитування та податкових пільг, що сприятиме доступності сертифікації для виробників. Акцентовано увагу на важливості інноваційних технологій, маркетингових стратегій та освітніх кампаній для популяризації органічної продукції. Видокремлено перспективи розширення експорту українських органічних продуктів та розвиток внутрішнього ринку. Запропоновано комплексний підхід для подолання викликів, що забезпечить підвищення конкурентоспроможності виробників, зміцнення позицій на міжнародній арені та сприятиме сталому розвитку аграрного сектору України. The article explores the essence of the "organic products" category and its importance for the sustainable development of agriculture. The main advantages of organic products are highlighted, including environmental friendliness, natural origin, and health benefits, which drive growing demand both in domestic and international markets. The study analyzes key challenges for the development of the organic products market in Ukraine, such as the high cost of certification, limited consumer awareness, logistical difficulties, and compliance with international standards. The need for governmental support, including subsidies, preferential loans, and tax benefits, is substantiated to make certification more accessible for producers. Emphasis is placed on the importance of innovative technologies, marketing strategies, and educational campaigns for promoting organic products among consumers. The paper identifies the prospects for expanding the export of Ukrainian organic products and developing the domestic market, considering the increasing global demand for healthy and eco-friendly food. A comprehensive approach to overcoming these challenges is proposed, which involves fostering collaboration between producers, the government, and international organizations. This approach aims to enhance the competitiveness of Ukrainian organic producers, strengthen their positions in global markets, and promote the sustainable development of Ukraine's agricultural sector. Moreover, the paper underscores the role of investments in logistics infrastructure, digital platforms, and precision farming technologies as critical drivers of efficiency and competitiveness. The adoption of block chain technologies for product traceability is also emphasized as a key factor in building consumer trust and improving transparency in production processes. The research concludes that the implementation of a holistic strategy that combines innovative solutions, state support, and effective marketing tools will ensure the stable growth of the Ukrainian organic products market, contributing to the global recognition of Ukrainian producers and the overall improvement of public well-being.
Development of t he organic products market in Ukraine: problems, prospects, and way s to address them
Keywords: органічна продукція; organic products; експорт; export; внутрішній ринок; domestic market; маркетингова стратегія; marketing strategy; інновації; innovations; державна підтримка; government support; логістика; logistics